Trend of Blood Groups and Rh Factor in the District Swabi (Medical Forum Monthly, 2024)
Objective: To determine frequency of ABO and Rh (D) blood groups among blood donors in district Swabi.Study Design: Observational / descriptive study.Place and Duration of Study: The study was conducted at BGKMC Hospital in collaboration with physiology Department, GKMC from 1st January 2015 to 31st December 2015.Materials and Methods: A total of 2120 healthy adult, blood donors (both volunteer and directed) from district Swabi were included. The data was collected from the record of Bacha Khan Group of Teaching hospitals in collaboration with department of Physiology. Results: Among ABO blood groups “B” (31.42%) was the most prevalent, followed by “A” (30.47%), “O” (29.53%) and “AB” (8.58%). Group Rh positive (93.11%) was more prevalent than Rh negative (6.88%). Similarly B+ive (28.76%) was most frequent followed by A+ive (28.41%), O+ive (27.64%), AB+ive (8.3%), B-ive (2.64%), A-ive(2.08%), O-ive( 1.89%) and AB-ive ( 0.28%).Conclusion: Blood group 'B' was most frequent among the ABO blood groups and Rh (D) positive among Rh blood groups while B+ive was the most frequent blood group in the study population.